PENGARUH PENGETAHUAN PERPAJAKAN, PEMAHAMAN PERPAJAKAN DAN KESADARAN DALAM MELAKSANAKAN KEWAJIBAN PERPAJAKAN TERHADAP PENERAPAN PAJAK UMKM (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine and analyze the influence of tax knowledge, understanding of taxation and awareness in carrying out tax obligations on the application of UMKM taxes. The population in this study is the Brebes tax office. The sampling method in this study was convenience sampling. Based on this method, the sample used in this study was 100 samples. To find out the linkages in this study, the statistical test was processed using SPSS version 23. The results of this study indicate that partial taxation knowledge has a significant effect on UMKM tax implementation, understanding of taxation and awareness in implementing tax obligations partially has no significant effect on UMKM tax implementation. Overall knowledge of taxation, understanding of taxation and awareness in carrying out tax obligations simultaneously has a significant effect on the application of UMKM taxes.